Analisis Pengembangan Wirausaha Lokal di Propinsi Riau - pailis, eka armas; fathoni, ahmad fauzan; ashrofillah, fuad (Komunitas Manajemen Kompetitif, 2016)
The development of an entrepreneurial-based local economic development outlined for 6 districts / cities that we studied. Determination of the commodity is determined by predetermined criteria, and the determination of these criteria is based on the objectives to be achieved in the development of local entrepreneurship. To obtain uniformity and consistency in the process of establishing a commodity, then each of the criteria used in all districts / cities are the same. Through the analysis using the formula LQ with survey data in the field is known that one of the characteristics of entrepreneurship is to act on business opportunities, business opportunities can be obtained from looking at and analyzing the following three potentials, namely: availability of natural resources, availability of human resources and Market Potential. Keywords: Local Entrepreneur, Location quation